2008
DOI: 10.1111/j.1365-4632.2008.03663.x
|View full text |Cite
|
Sign up to set email alerts
|

Antistreptococcal treatment of guttate psoriasis: a controlled study

Abstract: There was no statistically significant improvement in streptococcus associated guttate psoriasis with or without a course of oral penicillin or erythromycin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 11 publications
0
20
0
2
Order By: Relevance
“…Based on these results, it has been suggested that therapies targeting the streptococcus can be beneWcial for patients with psoriasis. Although anti-streptococcal management, such as antibiotics and tonsillectomy, have frequently been advocated for patients with recurrent psoriasis [5,19], there is to date no good evidence that either intervention is beneWcial [6,15,16].…”
Section: Discussionmentioning
confidence: 99%
“…Based on these results, it has been suggested that therapies targeting the streptococcus can be beneWcial for patients with psoriasis. Although anti-streptococcal management, such as antibiotics and tonsillectomy, have frequently been advocated for patients with recurrent psoriasis [5,19], there is to date no good evidence that either intervention is beneWcial [6,15,16].…”
Section: Discussionmentioning
confidence: 99%
“…Penicillin, Makrolidantibiotika (Erythromycin, Roxithromycin, Clarithromycin) alleine oder in Kombination mit Rifampicin und bestanden in der Regel in einer Kurzzeittherapie von 10-14, maximal 30 Tagen. Während die offenen, unkontrollierten Studien durchaus eine Besserung der Psoriasis unter Antibiotikatherapie sowohl bei akut-exanthematischer als auch chronisch-stationärer Psoriasis beobachteten, war bei den beiden kontrollierten Studien kein Einfluss auf den Krankheitsverslauf nachweisbar [9,22,36,37,42,45,47,58]. In einer unkontrollierten Studie wurde der Einfluss einer Dauertherapie mit Depotpenicillin an 30 Patienten untersucht.…”
Section: Antibiotische Therapie Und Psoriasisunclassified
“…This could be linked again with a better prognosis of patients with AGP in acute flares. Clinical studies suggest that a clear history of pharyngitis is presented in 19-82% and serological evidence in 54-93% [24][25][26] . A previous study found that patients with elevated ASLO titers had a better clinical course [5] .…”
Section: Discussionmentioning
confidence: 99%
“…We did not routinely perform pharyngeal cultures or determine streptococcal antibodies in patients with AGP because most of them were cured or being treated when attending our outpatient clinic. Only patients with symptoms of pharyngitis were prescribed antibiotics as no benefits of adding antibiotics to the treatment of AGP without previous pharyngitis have been demonstrated [26] .…”
Section: Discussionmentioning
confidence: 99%